2008
DOI: 10.1007/s10554-008-9380-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of left main coronary artery disease among patients referred to multislice computed tomography coronary examinations

Abstract: We have evaluated the prevalence of left main coronary artery disease (LMCAD) among patients referred to multislice computed tomography (MSCT) coronary angiography examinations. The study Group comprised of 1,000 consecutive patients (750 male and 250 female; mean age 53+/-12 years) who underwent successful 64-slice MSCT examinations. Left main coronary artery (LMCA) was classified into three Groups: normal LMCA; nonsignificant LMCAD with coronary plaques resulting in obstructions Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Despite the fact that significant left main disease (LMD) is a rather uncommon finding in patients with stable [ 1 ] or unstable [ 2 ] coronary artery disease (CAD), a significant narrowing of the LM is related to a potentially large area of ischemia leading to high-risk adverse cardiac events. The traditional approach for the management of LMD includes coronary artery bypass grafting (CABG), particularly if additional risk factors of an unfavorable outcome of percutaneous coronary intervention (PCI) occur.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that significant left main disease (LMD) is a rather uncommon finding in patients with stable [ 1 ] or unstable [ 2 ] coronary artery disease (CAD), a significant narrowing of the LM is related to a potentially large area of ischemia leading to high-risk adverse cardiac events. The traditional approach for the management of LMD includes coronary artery bypass grafting (CABG), particularly if additional risk factors of an unfavorable outcome of percutaneous coronary intervention (PCI) occur.…”
Section: Introductionmentioning
confidence: 99%
“…In the present issue of the International Journal of Cardiovascular Imaging Gemici et al [37] evaluated the prevalence of left main disease in 1,000 patients referred to MSCT (64-slice) coronary angiography. Left main coronary artery was classified into three groups: (1) normal left main coronary artery, (2) nonsignificant left main disease with coronary plaques resulting in \50% luminal stenosis, and (3) significant left main disease corresponding to [50% luminal stenosis.…”
mentioning
confidence: 99%
“…In that particular study, Pundziute et al [24] showed an 8% one-year event rate for patients with nonobstructive CAD versus 0% for patients without any signs of CAD. The study by Gemici et al [37] adds therefore important information to the capability of MSCT in assessing local plaque burden in patients with left main disease, in particular in those patients with non-significant left main disease. Timely detection of atherosclerosis of the left main coronary artery will therefore become a major challenge.…”
mentioning
confidence: 99%